Overview of Poverty Mentality, Social Assistance Interpretation, and Anomalies among Beneficiary Families of Direct Cash Assistance (BLT) in Bondowoso, East Java - Wahyuningsih, Rani Destia; Salsabila, Amelia Eka; Farhan, Ahmad Dhiauddin; Sulistyowenny, Shofialimah; Putri, Eke Rena Setia Poppy Billa Adawiyah; Muslihati (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
Bondowoso Regency is one of the areas in East Java with a high level of extreme poverty. The government, as a policy holder, has allocated funds to address this issue. Cash assistance in the form of Direct Cash Assistance (BLT) has been distributed on a large scale to alleviate poverty. However, poverty and the recipients of BLT in Bondowoso Regency continue to increase from year to year. Researchers indicate the presence of other factors within the community that perpetuate poverty, known as poverty mentality. Poverty Mentality is defined as the mindset and attitude of individuals who see themselves as financially poor and limited, leading them to feel trapped in a cycle of negative thinking and struggling to overcome adversity. This study aims to describe Poverty Mentality among BLT recipients and identify the meaning of BLT for them. The research uses phenomenological research methods with snowball sampling techniques. The Atlas.ti tool is also used to enhance research objectivity. The research findings show that the depiction of Poverty Mentality can be identified through the cognitive, emotional, and behavioral tendencies of informants who show a tendency to become complacent with the assistance provided. Meanwhile, the meaning of BLT itself is categorized into six aspects: a source of income, provision, opportunity opener, right of the poor, privilege, and savior. On the other hand, researchers have found anomalies among BLT recipients in Bondowoso, which may be a concern for local policymakers.